2019
DOI: 10.26717/bjstr.2019.21.003583
|View full text |Cite
|
Sign up to set email alerts
|

Missed Diagnosis and the Development of Acute and Late Lyme Disease in Dark Skinned Populations of Appalachia

Abstract: Background: Lyme Disease (LD) is the most commonly reported vector-borne disease in the United States, affecting over 300,000 people in the United States each year. If early LD goes undetected or is inadequately treated, the causative spirochete bacteria, Borrelia burgdorferi, can disseminate throughout the body and cause chronic symptoms that will characterize a patient with late LD. The incidence of LD is generally reported at a higher rate in light-skinned patients as compared to dark-skinned patients.Aim: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…An important example is the early erythema migrans rash that occurs with Lyme disease. It was thought that Lyme disease manifested more aggressively in Black patients, with multiorgan development and worse outcomes, but recent research has shown that these actually result from diagnostic delays because doctors are unable to recognize erythema migrans in darker skin 4 . To overcome these issues, medical schools need to acknowledge limitations in the demographic representation being used for course materials.…”
mentioning
confidence: 99%
“…An important example is the early erythema migrans rash that occurs with Lyme disease. It was thought that Lyme disease manifested more aggressively in Black patients, with multiorgan development and worse outcomes, but recent research has shown that these actually result from diagnostic delays because doctors are unable to recognize erythema migrans in darker skin 4 . To overcome these issues, medical schools need to acknowledge limitations in the demographic representation being used for course materials.…”
mentioning
confidence: 99%